Training on using the website of Batuah Village, Loa Janan, Kutai Kartanegara - Karyo Budi Utomo; Bambang Cahyono (Community Empowerment, 2022)
The profile of Batuah village and its potential have not been published in a structured manner until now. Information is still distributed to the public in the traditional manner. Furthermore, it is difficult for potential investors to obtain accurate information. The use of information technology as a front line in improving public information delivery has not been fully exploited. To address these issues, the service team created the Batuah village website and provided training to village staff, RT heads, and BPD personnel on how to use it. As a result, it is easier for the Batuah village government to communicate information to the community, stakeholders can easily discover Batuah village's potential, and the community can easily obtain the most up-to-date information on village government policies.